In Silico Molecular Docking and Toxicity Studies of Bioactive Fucoidan Compound from Brown Seaweed as Potential of Antihypertensive - Agus Kurniawan; Siswandono Siswandono; Esti Mumpuni; Syamsudin Abdillah (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Angiotensin Converting Enzyme (ACE) is an enzyme that can convert angiotensin 1 to angiotensin 2 peptide, which is a strong vasoconstrictor that causes hypertension. Fucoidan (4,5-dihydroxy-2,6-dimethyltetrahydro-2H-pyran-3-yl hydrogen sulfate) is one of the polysaccharide chemical compounds found in seaweed and is reported to have the ability to inhibit ACE activuty in vitro. The aim of this study is to predict of the binding interaction between fucoidan and amino acids in ACE and to use the native captopril ligand (MCO702) as the standard ligand. Analysis of the molecular docking of fucoidan and captopril compounds against ACE (1UZF) using Molegro 6.0 and Chemoffice Professional 17.1 Software and for toxicity analysis using pkCMS online tools. The results of the docking prediction showed that fucoidan had MolDock and Rerank Score values of -82.311 kcal/mol and -70.872 kcal/mol, respectively, which were not much different from captopril, namely -84.816 kcal/mol and -74.758 kcal/mol. Fucoidan and captopril are also easily absorbed and have good permeability and are classified as low toxicity, but are dangerous if ingested in the 2000 LD50≤ 5000 mg/kg range. Fucoidan has the potential as a candidate for antihypertensive drugs because it is predicted that in silico has the same ability as captopril.